Dipping in Ambulatory Blood Pressure Monitoring Correlates With Overnight Urinary Excretion of Catecholamines and Sodium. Issue 9 (10th February 2016) - Därr, Roland; Bursztyn, Michael; Pamporaki, Christina; Peitzsch, Mirko; Siegert, Gabriele; Bornstein, Stefan R.; Eisenhofer, Graeme
Abstract : Nondipping blood pressure (BP) is associated with increased morbidity and mortality. This study examines the relationship of "dipping" in 24‐hour ambulatory BP monitoring (ABPM) with awake and sleeping urinary norepinephrine (NE) and epinephrine (EPI), and that of urinary NE and EPI with urinary sodium (UNa). Fifty nondippers and 65 dippers were included in the present study. Collected data included age, sex, body mass index, history of hypertension, current antihypertensive treatment, ABPM data, and NE, EPI, and UNa values. Hierarchical multiple regression analysis with the night‐to‐day ratio (NDR) of systolic BP as a dependent variable showed that the composite term of the NDRs of urinary NE and EPI was a significant predictor for dipping. Results also show a differential role of NE and EPI in circadian UNa excretion in dippers and nondippers. These results indicate that the sympathetic nervous system is involved in the regulation of circadian BP variations and UNa excretion.